2017
DOI: 10.1111/jgh.13452
|View full text |Cite
|
Sign up to set email alerts
|

A noninvasive model to predict liver histology in HBeAg‐positive chronic hepatitis B with alanine aminotransferase ≤ 2upper limit of normal

Abstract: This study constructed a noninvasive model to predict liver histology in HBeAg-positive CHB with ALT ≤ 2ULN, which might reduce the clinical need for liver biopsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 30 publications
(63 reference statements)
0
13
1
Order By: Relevance
“…However, we did not find that other serum markers, such as ALT and AST, were significantly correlated with HIA. The difference between our study and other studies 8,31 may lie in the small sample size of our study. Nonetheless, the combined model exhibited a favorable performance in the test cohort (AUC, 0.911).…”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations
“…However, we did not find that other serum markers, such as ALT and AST, were significantly correlated with HIA. The difference between our study and other studies 8,31 may lie in the small sample size of our study. Nonetheless, the combined model exhibited a favorable performance in the test cohort (AUC, 0.911).…”
Section: Discussioncontrasting
confidence: 64%
“…4 However, prior studies have demonstrated that a significant number of patients with ALT <2 ULN may also have histologically significant HIA. [7][8][9] Thus, serum markers reveal a low accuracy for staging HIA and are susceptible to hepatic and extrahepatic conditions. 10 Magnetic resonance imaging (MRI) is a promising technique in abdominal imaging, especially in the evaluation of CLD and detection and characterization of focal lesions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, multiple noninvasive methods based on laboratory tests have been developed as surrogates to assess liver fibrosis, such as aspartate aminotransferase–platelet index (APRI), fibrosis index based on the four factors (FIB-4), Forns’ index [ 9 ], and Hui model [ 10 ]. Gao et al [ 11 ] had reported a noninvasive model, consisting of aspartate transaminase (AST), HBsAg, platelet, and albumin, to predict significant liver histology change [necroinflammatory activity grade ( G ) ≥ 2 or fibrosis stage ( S ) ≥ 2] in HBeAg-positive CHB with ALT ≤ 2ULN. Gao’s model had an area under the receiver operating characteristic curve of 0.868, which was significantly higher than APRI and FIB-4.…”
Section: Introductionmentioning
confidence: 99%
“…Serum AST had been widely used to evaluate liver necroinflammation due to its association with mitochondrial injury ( 7 ). Serum ALB is also associated with liver necroinflammation, as its production is affected by liver injury ( 21 ). In addition, ALT is commonly used to evaluate the severity of liver necroinflammation, with increases in ALT levels indicating histopathological changes in the liver, even in patients with ALT within the normal range ( 22 ).…”
Section: Discussionmentioning
confidence: 99%